Identification of the Life Cycle Rate of Flies in the Carcass of Rattus Norvegicus that is Exposed and Not Exposed to Sunlight in Determining the Post Mortem Interval - Suryo Wijoyo; Michelle Debora Nathasya Hartanti Aritonang (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The discovery of corpses represents the most common criminal case category in Indonesia, accounting for 35.46% or approximately 3,698 cases from early 2024 to September 20, 2024. Determining the post mortem interval (PMI) is therefore essential in forensic investigations. One method used to estimate PMI is forensic entomology through the analysis of insect life cycles developing on corpses, particularly flies. Environmental factors, such as sunlight exposure, may influence the development rate of flies and affect the accuracy of PMI estimation. Objective: This study aimed to identify differences in the development rate of the fly life cycle on Rattus norvegicus carcasses exposed and not exposed to sunlight. Methods: This study employed a quasi-experimental method using a posttest-only non-equivalent control group design. Observations were conducted twice daily to record and collect specimens from each developmental stage of flies, including eggs, larvae, pupae, and adult flies, on carcasses exposed and not exposed to sunlight. Results: The findings demonstrated significant differences in the development rates of second instar larvae, third instar larvae, pupae, and adult flies between carcasses exposed to sunlight and those not exposed, with p-values < 0.05. Conclusion: Sunlight exposure significantly affects the development rate of the fly life cycle on Rattus norvegicus carcasses. These findings indicate that environmental exposure should be considered in forensic entomology analysis to improve the accuracy of PMI estimation.